Predisposing factors for enlargement of intracerebral hemorrhage in patients treated with warfarin - Yasaka, Masahiro; Minematsu, Kazuo; Naritomi, Hiroaki; Sakata, Toshiyuki; Yamaguchi, Takenori (Thrombosis and Haemostasis, 2003)
To elucidate predisposing factors for enlargement of intra-cerebral hematoma (ICH) during warfarin therapy, we reviewed 47 patients on warfarin who developed acute ICH and determined relationships among ICH enlargement, INR reversal and clinical data. Among 36 patients treated to counteract the effects of warfarin within 24 h of onset, ICH increased in 10 patients (enlarged group), but remained unchanged in the remaining 26 (unchanged group), while ICH remained unchanged in another 11 patients in whom the effect of warfarin was reversed after 24 h. The international normalized ratio (INR) was counteracted immediately in 11 patients treated with prothrombin complex concentrate (PCC) but gradually in the other 36 treated by reducing the dose of warfarin, or by administering vitamin K or fresh frozen plasma. Multivariate analysis with a logistic regression model showed an INR value <2.0 at admission or for 24 h after immediate INR correction with PCC prevented ICH enlargement (OR 0.069, 95%CI 0.006-0.789, p = 0.031). An INR value of >2.0 within 24 h of ICH seems an important predisposing factor for ICH enlargement.
Keywords: Intracerebral hematoma; warfarin; prothrombin complex concentrate; international normalized ratio